Toward Universal Half‐Saturation Coefficients: Describing Extant KS as a Function of Diffusion. (1st May 2015) - Shaw, Andrew; Takacs, Imre; Pagilla, Krishna; Riffat, Rumana; DeClippeleir, Haydee; Wilson, Christopher; Murthy, Sudhir
ABSTRACT: : Observed (extant) K S is not a constant and it is strongly influenced by diffusion. This paper argues that diffusion can be used to describe bacterial kinetic effects that are sometimes attributed to "K‐strategists" and, in fact, the physics of the system is the dominant mechanism affecting the apparent (extant) K S —not intrinsic biological characteristics—in real water resource recovery facility systems. Four different biological processes have been modeled using the "porter‐diffusion" model that was originally developed byPasciak and Gavis (1974) for aquatic systems. The results demonstrate that diffusion is the dominant mechanism affecting K S in all four biological processes. Therefore, the authors argue that for treatment processes in which substrate concentrations are low, it is important to consider shifting to variable extant K S values or explicitly modeling the effects of diffusion.